Highly efficient povidone-phosphotungstic acid catalyst for the tandem acetalization of aldehydes to bis- and tris(indolyl)methanes - Kamble, Sumit B.; Swami, Rameshwar K.; Sakate, Sachin S.; Rode, Chandrashekhar V. (ChemPlusChem, 2013)
A novel, nonleachable hybrid of heteropoly acid and polyvinylpyrrolidone (or povidone) catalyzes the acetalization of aldehydes in methanol at room temperature followed by reaction with indole to give bis(indolyl)methanes (BIMs) and tris(indolyl)methanes (TIMs) in quantitative yields (90-97%). The catalyst was shown by pyridine FTIR spectroscopy to possess BrOnsted acidity, and the hybrid formation was confirmed by XRD and (PNMR)-P-31 studies. Friedel-Crafts alkylation of indole as well as the tandem synthesis of BIMs and TIMs were established with several types of carbonyl and indole substrates to give the corresponding products quantitatively. The catalyst was recycled efficiently for three successive runs without losing its original activity.
Keywords: acetals; Acidity; aldehydes; heterogeneous catalysis; heteropoly acids

MCM-41-supported phosphotungstic acid-catalyzed cleavage of C-O bond in allyl aryl ethers - Sakate, Sachin S.; Kamble, Sumit B.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (New Journal of Chemistry, 2017)
Removal of the protecting allyl group from allyl aryl ethers in the presence of other oxygen protecting groups was successfully achieved using a solid acid supported on the high surface area material MCM-41. The catalyst showed excellent activity in the presence of various electron withdrawing, electron donating, and oxidizable functional groups. The methodology is also very useful for the removal of protecting allyl groups of various natural products such as vanillin, isovanillin, and other oxygen functionalized aldehydes and ketones.

Cascade synthesis of dihydrobenzofuran via claisen rearrangement of allyl aryl ethers using FeCl 3 /MCM-41 catalyst - Sakate, Sachin S.; Shinde, Suhas H.; Kasar, Gayatri B.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Journal of Saudi Chemical Society, 2018)
Dihydrobenzofuran as one of the active ingredients of the naturally occurring motif is synthesized by using in situ generation of ortho allyl phenols. Aryl allyl ethers on reacting with catalytic amounts of non noble metal iron (III) chloride supported on MCM-41 under moderate reaction conditions yield dihydrobenzofuran. First step via Claisen rearrangement gives ortho allyl phenol followed by its in situ cyclization to yield dihydrobenzofuran in very good yields. Both Lewis as well as Brønsted acidity of the catalyst as evidenced by Py-FTIR studies was found to catalyze the cascade synthesis of dihydrobenzofuran. The scope of the present strategy was successfully demonstrated for several substrates with varying electronic effects for the synthesis of corresponding dihydrobenzofuran with high yields in a range of 71-86%.
Keywords: Aryl allyl ether; Claisen rearrangement; Dihydrobenzofuran; Ferric chloride; MCM-41

Water-promoted surface basicity in FeO(OH) for the synthesis of pseudoionones (PS) and their analogues - Vernekar, Dnyanesh; Sakate, Sachin S.; Rode, Chandrashekhar V.; Jagadeesan, Dinesh (Journal of Catalysis, 2019)
Use of Iron oxyhydroxide (gamma-FeO(OH)) as a robust catalyst for the synthesis of important intermediates like pseudoionones and their analogues through the C-C bond formation reactions like knoevenagel and aldol condensation is explored. These motifs are the building blocks for the construction of the sesquiterpenes as well as the diterpenes such as retinoic acid, Vitamin A etc. Iron oxyhydroxide (gamma-FeO(OH)) was synthesized and well characterized using XRD, FT-IR, TEM, XPS and adsorption studies to establish the catalytic activity. A thorough investigation on the nature of basic sites and the role of water as a promoter was explored based on dye adsorption, in situ methanol dissociation and CO2 adsorption studies. The catalyst also showed a wide range of substrate scope with active methylene groups involving various functional groups such as cyanides, esters and acetophenones along with its stability and reproducibility. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: Bronsted basicity; Iron (III) oxyhydroxide; Knoevenagel condensation; Pseudoionones; Surface hydroxyl groups